COVID-19 on the Telecommunications Industry Stock Market Performances: An Event-Study Approach - Ariantika, Pratita Garnis; Davianti, Arthik (International Journal of Social Science and Business, 2021)
This study aims to analyze the knowledge quality of the COVID-19 pandemic event regarding the Indonesian stock market's performance as seen from the average abnormal return before and after the first case of COVID-19 Indonesia on March 2, 2020. The research design used in this study is an event study. Three samples used in this research are companies engaged in the telecommunications subsector in the Indonesia Stock Exchange. The technique of sampling that was used in the research was purposive sampling. The study focused on the window period 15 days before and 15 days after the event date. Hypothesis testing is done by using paired sample t-test on data that is typically distributed and the one-sample Wilcoxon signed-ranked test on data that is not yet normally distributed. The result obtained is that there are no significant differences before and after the announcement of the first case of COVID-19 in Indonesia.